The Use of the Ruang Belajar Application as a Supporting Tool for Creative Islamic Religious Education (PAI) Learning Strategies at SMAN 1 Yosowilangun - Nur Azizah; Dhevin MQ Agus Puspita W (-, 2026)
This study aims to analyze of the use of the Ruang Belajar Application (Rubel) as a support for creative Islamic Education (PAI) learning strategies at SMAN 1 Yosowilangun. This research employed a qualitative approach, with data collected through observation, interviews, documentation, and supported by survey data from 242 twelfth-grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the use of the Rubel Application has a positive impact on the PAI learning process, as reflected in increased student engagement, interest, and understanding. Learning becomes more interactive and varied through the integration of text, video, and project-based assignments. The implementation of the MODERAT learning strategy (Muhasabah, Observation, Deepening Material, Elaboration, Actualization Space, Affirmation and Reflection, and Competency Test) effectively organizes the learning process in a structured manner and encourages active student participation. However, challenges were identified, including limited internet access and varying levels of students’ digital literacy. To address these issues, adaptive strategies such as hotspot sharing and collaborative group work were implemented. In conclusion, the Ruang Belajar Application functions not only as a learning medium but also as an integrated system that supports the development of creative, flexible, and student-centered PAI learning strategies.